Additional oncological benefit of photodynamic diagnosis with blue light cystoscopy in transurethral resection for primary non‐muscle‐invasive bladder cancer: A comparative study from experienced institutes. Issue 3 (13th January 2023) - Miyake, Makito; Nishimura, Nobutaka; Nakahama, Tomonori; Nishimoto, Koshiro; Oyama, Masafumi; Matsushita, Yuto; Miyake, Hideaki; Fukuhara, Hideo; Inoue, Keiji; Kobayashi, Keita; Matsumoto, Hiroaki; Matsuyama, Hideyasu; et al.
Abstract: Objectives: The objective of this work is to evaluate the additional oncological benefit of photodynamic diagnosis (PDD) using blue‐light cystoscopy in transurethral resection (TURBT) for primary non‐muscle‐invasive bladder cancer (NMIBC) based on the International Bladder Cancer Group (IBCG)‐defined progression and the subsequent pathological pathways. Patients and Methods: We reviewed 1578 consecutive primary NMIBC patients undergoing white‐light TURBT (WL‐TURBT) or PDD‐TURBT during 2006–2020. One‐to‐one propensity score‐matching was performed using multivariable logistic regression to obtain balanced groups. IBCG‐defined progression of NMIBC included stage‐up and grade‐up as well as conventional definitions such as the development of muscle‐invasive BC or metastatic disease. Nine oncological endpoints were evaluated. Sankey diagrams were generated to visualize follow‐up pathological pathways after the initial TURBT. Results: Comparison of event‐free survival between the matched groups revealed that PDD use decreased the bladder cancer recurrence risk and IBCG‐defined progression risk, whereas no significant difference was noted in conventionally defined progression. This was attributable to a reduced risk of stage‐up, from Ta to T1, and grade‐up. Sankey diagrams of the matched groups showed that patients with primary Ta low‐grade tumour and first‐recurrence Ta low‐grade tumour did not have bladder recurrence or progression, while some of those in the WL‐TURBT group developed recurrence after treatment. Conclusions: The multiple survival analysis demonstrated that the risk of IBCG‐defined progression was significantly decreased by PDD use in NMIBC patients. Sankey diagrams revealed possible differences in pathological pathways after the initial TURBT between the two groups, demonstrating that repeated recurrence could be prevented by PDD use.